-9n+(n-7)=6n-231

Simple and best practice solution for -9n+(n-7)=6n-231 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9n+(n-7)=6n-231 equation:


Simplifying
-9n + (n + -7) = 6n + -231

Reorder the terms:
-9n + (-7 + n) = 6n + -231

Remove parenthesis around (-7 + n)
-9n + -7 + n = 6n + -231

Reorder the terms:
-7 + -9n + n = 6n + -231

Combine like terms: -9n + n = -8n
-7 + -8n = 6n + -231

Reorder the terms:
-7 + -8n = -231 + 6n

Solving
-7 + -8n = -231 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-7 + -8n + -6n = -231 + 6n + -6n

Combine like terms: -8n + -6n = -14n
-7 + -14n = -231 + 6n + -6n

Combine like terms: 6n + -6n = 0
-7 + -14n = -231 + 0
-7 + -14n = -231

Add '7' to each side of the equation.
-7 + 7 + -14n = -231 + 7

Combine like terms: -7 + 7 = 0
0 + -14n = -231 + 7
-14n = -231 + 7

Combine like terms: -231 + 7 = -224
-14n = -224

Divide each side by '-14'.
n = 16

Simplifying
n = 16

See similar equations:

| -30=-2(-1n+3) | | P^3+4p^2+8p+32=0 | | 9y=7y+8 | | -y-2(2y-1)=5(1-y) | | 8=10-2n | | 3x^2-5=54 | | 8=10-2 | | 8x-9y+73= | | 4(x-1)-x=23 | | Y=-2x^2+4x+8 | | x+3.5x=9.90 | | -6k-7=-(6k-7) | | 10=6+2w | | 30x^3-24x^2-15x+12=0 | | 2x-84=7x-4 | | 8(p-3)=8(1+p) | | 3g-5=1 | | x-14+2x=16 | | (2y-1)(y-2)=6 | | 9x+84=12 | | 5y+13=2y+22 | | 6x-4-4x=2x-4 | | 4x+15=24 | | 24-64n=-8(-3+8n) | | 7x-13=42 | | 4x^2-17x-15=30 | | -85=5(2n-3) | | 3x+10=2x-x+18 | | 11x+25=78 | | -2(z-3)-4=18 | | -2-(12x+8)+17=3+x-(13x-4) | | -12z-29=5(z+6)-195 |

Equations solver categories